Material aspects of reading in Ancient and Medieval cultures: materiality, presence and performance - Krauß, Anna H.; Leipziger, Jonas; Schücking-Jungblut, Friederike (Materiale Textkulturen, 2020)
Frontmatter --Acknowledgements --Contents --Material Aspects of Reading and Material Text Cultures --Material Aspects of Rituals Beyond Their Instructions --Scribal Production and Literacy at Qumran --Scribal Habits and Scholarly Texts --Reading Psalm and Prayer Manuscripts From Qumran --Reading the Songs of the Sabbath Sacrifice --Reading Material Features of Qumran Tefillin and Mezuzot --Reading an Opisthograph at Qumran --Codices des Typs C und die Anfänge des Blätterns --Ancient Jewish Greek Practices of Reading and Their Material Aspects --Reading Early New Testament Manuscripts --What Ancient Christian Manuscripts Reveal About Reading (and About Non-Reading) --Reading Regularly --Encountering the Grotesque --Notes on Contributors --Indices